Síntese e avaliação da atividade antibacteriana de derivados 1,2,3-triazólicos e éteres do paeonol - Figueroa, Laura Patricia Rocha (2022)
The multidrug-resistant (MDR) bacteria Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) cause different infections and diseases that affect humanity for a long time, and have been emerging. Today, these infections and diseases have been a growing global health problem that has led to increased morbidity and mortality. The growing emergence of multidrug-resistant bacteria has highlighted the need for the development and discovery of new antibacterial compounds. In this context, a series of paeonol 1,2,3-triazole derivatives and ethers were synthesized using a click chemistry reaction and nucleophilic substitution catalyzed by copper(I)-azide-alkyne (CuAAC). Paeonol has been a widely studied natural product due to its diverse biological activities, as well as its derivatives. Three ether derivatives (two unpublished) and ten triazole derivatives (six unpublished) of paeonol were obtained, which were determined by NMR, FT-IR, FT-ICR MS and six of them by X-rays, being the first study of this type presented for these compounds. All synthesized compounds were evaluated as potential antibacterial agents against Staphylococcus aureus and Escherichia coli, obtaining a minimum inhibitory concentration (MIC) above 100µg mL-1. The results showed that click chemistry and nucleophilic substitution were very useful to obtain new paeonol triazole derivatives and ethers and the products were obtained in yields from 21.30% to 98.49%. The advantages of these reactions (reaction time, low impurities) carried out show that it is advisable to use the method for the production of new derivatives and thus assist in the discovery of new drugs.